Sadyattes and His Niece: a Note on Suda α 1423 and α 441 - Paradiso, Annalisa (Histos, 2015)
This paper deals with two Suda-entries on Lydian kings, α 1423 and α 441, the latter of which reproduces two lines of the former. Both α 441 and α 1423, along with their source Nicolaus of Damascus FGrHist 90 F 63 and Xenophilus FGrHist 767 F 1, require a textual emendation: ἀδελφιδήν must be restored in all cases in place of the transmitted ἀδελφήν.